A Longitudinal Study: Correlation Between Physical Activity and Stress Level Among Undergraduate Students in IPB University - Suryono, Alfina Zalfa; Ananta, Muhammad Isa; Hapsari, Eno Aulia; Soleha, Ismayanti; Ramadhan, Muhammad Roykhan Dwidasa; Zakaria, Muhammad Dafa; Widayati, Kanthi Arum (Departemen Biologi, Institut Pertanian Bogor, 2024)
The COVID-19 pandemic-related restrictions on physical activity outside can cause changes in physical activity in humans compared to before the pandemic. Differences in levels of physical activity are frequently associated with changes in stress levels, including in students. However, no longitudinal research has been conducted on the relationship between physical activity and stress levels in undergraduate students using the same respondents in different settings. This study aimed to assess the relationship between physical activity and stress levels in Indonesian students and to assess its consistency under different conditions. The data was collected from 81 undergraduate students in IPB University in two sampling phases: 2021 (during the Covid-19 pandemic) and 2023 (after the pandemic). The International Physical Activity Questionnaire (IPAQ) was used to assess the prevalence of physical activity, and the Perceived Stress Scale (PPS) was used to assess students’ perceived stress. The findings revealed that there were no differences in physical activity and stress levels between the two sampling phases. There was no significant relationship between physical activity and stress levels at either sampling time. These findings suggest that stress level at a certain level does not show any link to physical activity of the students.